Typing of Acinetobacter baumannii Isolates from some Iraqi Children infected with Head Lice - Eman N. Najii (Journal of Global Pharma Technology, 2017)
Head lice invasion a worldwide health care problem, which obligatory human hematophagous ectoparasites belong to pediculide family, it caused by pediculus humans capitis [1] in fact the USA was recorded 6-12 million of head lice invasion appeared every year [2].